Implementasi Pembelajaran Teknologi Informasi dan Komunikasi (TIK) dalam Meningkatkan Kemampuan Literasi Digital Peserta Didik Paket A di Homeschooling Pena Surabaya - Hanifah, Nia; Yusuf, Ali (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The purpose of this research is to determine the process of implementing information and communication technology (ICT) learning in improving the digital literacy skills of package A students at Homeschooling Pena Surabaya. This research uses a descriptive qualitative type and approach. The data colllection techniques used were in depth interviews, participant observation, and documentation. The result of this research show that the implementation of ICT learning is applied to package A students through learning planning procedures, learning implementation, and learning evaluation and students can understand icons on microsoft excel, students can search for keywords, students can create microsoft excel assignment output, and students are able to communicate via email and have a positive view of using the digital internet. The supporting factors are the competence of the tutor, the interest of the students, and support of the family environment. Apart from that, the inhibiting factors are signal problems, limited learning time, and differences in technological devices.